Effect of Sacral Nerve Stimulation on Detrusor Overactivity among Spinal Cord Injury - Deebika, .; Kumaresan, Abathsagayam; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Priyadharshini, Kumar; Vinodhkumar, Ramalingam (INTI International University, 2023)
Background and aim: Spinal cord injury is still a leading cause of disability. Nowadays, there is a high level of illness and death. According to the National Spinal Cord Injury Statistical Centre, every year, 40 new instances per million people are documented. Over 80% of these people have some form of bladder dysfunction. Some studies suggest that sacral nerve stimulation can help with bladder dysfunction. Hence, this study was aimed to identify the benefit of sacral neuronal activity on detrusor over activity among spinal cord injury. Material & methods: This pilot test was analysed at the Saveetha Institute of Medical Science and Technology (SIMATS). For a four-week period, 15 patients with post-spinal cord injury were chosen. Patients were evaluated with overactive bladder symptoms score before the initiation of treatment. The patients were given with sacral nerve stimulation for 4 weeks 2 sessions per day. After 4 weeks of intervention patients were assessed with overactive bladder symptoms score as a posttest value. Result: The statistical analysis revealed a statistically significant improvement. The sacral nerve stimulation has been demonstrated to be efficacious in curing detrusor overactivity caused by spinal cord damage. Conclusion: This study emphasizes that sacral nerve stimulation improves bladder function in people with spinal cord injuries